Tembang Macapat Sebagai Metode Untuk Penanaman Dasar-Dasar Musikalitas - Wahyudiono, Teguh; Mulyanto, Mulyanto; Supriyadi, Slamet (Institut Seni Indonesia Yogyakarta, 2022)
ABSTRACT This research departs from a problem, namely that students of the Mangkunegaran Art Academy in Surakarta the II semester for the academic year 2021/2022 have difficulty understanding the musicality of the tembang macapat which includes titilaras and laya. Thus, this study aims to describe the learning process of the tembang macapat as an inculcation of the basics of student musicality in the students of the karawitan arts study program at the Mangkunegaran Art Academy in Surakarta. Researchers examine learning from the learning stages (pre, process, and post), learning components (objectives, materials, models, methods, media, and evaluation) and the basics of musicality including titilaras and laya. The research subjects are II semester students for the 2020/2021 academic year. The researcher chose a qualitative method in descriptive form by engaging directly with students and lecturers during the research process to obtain information and data about the learning process. The results of this study prove that there is an influence of the tembang macapat learning process on the cultivation of the basics of musicality in the form of theory and practice. This can be seen from the success of lecturers in instilling the basics of musicality to students as evidenced by 81.25% of students when presenting tembang macapat well in emphasizing titilaras and laya, due to various factors, namely basic conditions and student skills (eg the sound of sasap, blero, false